Study The Influence Of Light And Distance To Reduce Traffic Accident - Dayana, Indri (Invention: Journal Research and Education Studies, 2021)
Traffic accidents are something that every road user wants to avoid, but sometimes these traffic accidents occur suddenly because of poor road infrastructure or due to negligence of the road users themselves. At present there are widespread accidents in the traffic system, this is caused by many factors, one of which is the arrangement of lights and the distance between vehicles on the highway. The number of traffic accidents in Indonesia has increased every year. The number of traffic accidents in Indonesia is in line with the increasing number of motorized vehicles. Good lighting and distance allow people who drive to see objects that are done clearly, quickly and without unnecessary effort, especially adequate lighting gives the impression of a better appearance and a refreshing environment. Good lighting and distance can also provide higher efficiency, can increase productivity and reduce visual difficulties and pressure when driving. Conversely, poor lighting and distance will result in a high level of traffic accidents.